Pengujian Orgnanoleptik Sosis Ikan Lele (Clarias gariepinus) Campuran Pati Sagu Baruk (Arenga Microcarpa) dan Tepung Ubi Jalar Ungu (Ipomea batatas var Ayamurasaki) - Martha R.R. Rumaratu; Teltje Koapaha; Tineke Langi; Lucia Mandey (Universitas Sam Ratulangi, 2015)
ABSTRACT Sausage is a food that is popular and well known in all walks of life. Sausage is food made from finely chopped meat and spices given, entered into an elliptical wrapper in the form of animal gut or artificial wrapping with or without cooking, with or without smoked. Excipients commonly used in processed meat products are carbohydrates / starches. This study aims to fine the organoleptic characteristic of sausages catfish mixed by sagoo baruk starch and purple sweet potato flour and preferred by the panelists. This study uses a completely randomized design with sago baruk starch treatment and purple sweet potato flour. The results showed that avarege values of sausage catfish using sago baruk starch and purple sweet potato flour for taste is 3,67 (like), tekstur 3,72 (like), colour 3,56 (like), and smell 3,66 (like), are liked by panelist Keywords: sausage, catfish, sago starch baruk, purple sweet potato flour